P.179 Clinical trial readiness and validation of onsite and remote evaluation in valosin containing protein-associated multisystem proteinopathy - Alfano, L.; Peck, A.; Iammarino, M.; Patel, S.; Reash, N.; Almomen, M.; Mendell, J.; Sabo, B.; Long, A.; Pietruszewski, L.; Lowes, L.; Peck, N. (Neuromuscular disorders : NMD, 2022)
The purpose of our study was to validate functional assessments in patients with valosin containing protein-associated multisystem proteinopathy (VCP-MSP), previously known as inclusion body myopathy with Paget's Disease of the bone and frontotemporal dementia. VCP-MSP is a rare disorder of multisystemic involvement resulting in progressive weakness, bone disease, frontotemporal dementia, cardiac, respiratory, and/or bulbar dysfunction. Patient disease onset and presentation is heterogeneous, highlighting the need for a prospective clinical trial readiness study to inform future clinical trial design. In addition, we sought to prospectively compare the validity of in-home, remote assessments to those performed in the standardized clinic environment. Thirty-two subjects have enrolled to date (mean age: 53.1 years (range: 28-73)) with genetically-confirmed VCP-MSP. A battery of functional and patient-reported clinical outcome assessments (COA) was completed at each visit. Over 60% of the cohort demonstrated reduced sensation upon physical exam, with <15% having a diagnosis of peripheral neuropathy. Paget's disease of the bone was diagnosed in 20% of the cohort and frontotemporal dementia in <5%. COA performance was correlated with disease duration and genotype but not with age at visit highlighting the variability in the relationship between genotype and phenotype in VCP-MSP. Test-retest reliability was excellent within and between visit types (ICC≥0.8; P<0.001). Performance of most COA was the same across remote and onsite environments; two of the functional COA were slightly more variable in the home environment when compared to onsite visits, emphasizing the need for standardized equipment and furniture when implemented in clinical trials. Cohort level feasibility and cross-sectional performance of all COA, sensitivity to change and meaningful change on included assessments over 1-year will also be presented.